The Survival of Airasia During the Covid-19 Pandemic - Reddy, L. Sudershan; P V, Ranjith; Lim, Yu Cing; Kee, Daisy Mui Hung; Loo, Wen Ting; Cheah, Keng Tyng; Mak, Shuet Yee (AIBPM Publisher, 2021)
This research is to investigate the survival of AirAsia during the pandemic Covid-19. The findings will show how AirAsia faced challenges during the pandemic and ways to overcome them. This research underlined the challenges faced by AirAsia such as flight cancellation, decrease in demand, loss of new customers, and paying huge amounts of refunds. AirAsia used several ways such as controlling the operational cost, exploring new business, carrying out promotions, and applying for bank loans and weighing proposals. As a result, AirAsia’s financial problems would be solved by reducing operational costs and increasing the profit from other businesses.